2004
DOI: 10.1192/pb.28.6.225
|View full text |Cite
|
Sign up to set email alerts
|

A survey of workplace bullying of psychiatric trainees in the West Midlands

Abstract: Aims and MethodA postal survey was conducted to ascertain the prevalence of bullying behaviour experienced by psychiatric trainees in the West Midlands. Questionnaires were sent to 232 junior doctors, 76% of whom responded.ResultsIn the preceding year, 47% of trainees had experienced one or more bullying behaviours. Only 46% reported that they knew whom to contact if they were bullied. Foreign doctors were significantly less likely to take action when bullied than local doctors.Clinical ImplicationsWorkplace b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Female doctors and those from ethnic minorities were more likely to report being bullied 8 . In a survey of psychiatric trainees in the West Midlands, 47 per cent had experienced bullying within the last year, and again this was more likely among ethnic minorities and females 9 . A survey of doctors in training in hospitals in London found that 18 per cent had been subjected to bullying within their current post – reported prevalence among trainees who were female, more junior, and who were not UK graduates, was higher 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female doctors and those from ethnic minorities were more likely to report being bullied 8 . In a survey of psychiatric trainees in the West Midlands, 47 per cent had experienced bullying within the last year, and again this was more likely among ethnic minorities and females 9 . A survey of doctors in training in hospitals in London found that 18 per cent had been subjected to bullying within their current post – reported prevalence among trainees who were female, more junior, and who were not UK graduates, was higher 10 .…”
Section: Introductionmentioning
confidence: 99%
“…8 In a survey of psychiatric trainees in the West Midlands, 47 per cent had experienced bullying within the last year, and again this was more likely among ethnic minorities and females. 9 A survey of doctors in training in hospitals in London found that 18 per cent had been subjected to bullying within their current postreported prevalence among trainees who were female, more junior, and who were not UK graduates, was higher. 10 In 2006 the Postgraduate Medical Education and Training Board (PMETB) and the Conference of Postgraduate Medical Deans (COPMeD) surveyed trainees across the UK about their training posts.…”
mentioning
confidence: 99%
“…Bullying is commonly reported, with up to 84% of trainees reporting one or more bullying behaviours (Quine 2002). However, bullying was reported not just in macho specialties, but in psychiatry at 47% of trainees (Hoosen & Callaghan 2004) and even in palliative care at 40% of trainees (Keeley et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…On a broader front, workplace bullying (of which teaching by humiliation is a subset) is still apparently alive and well in training settings. In a study of psychiatric trainees nearly half had experienced one or more bullying behaviours in the preceding year, 4 although another recent survey of junior doctors suggested a lower (falling?) rate 5 …”
mentioning
confidence: 99%
“…Although ‘whistle‐blowing’ is increasingly encouraged, at both undergraduate and postgraduate levels, with anti‐bullying policies apparently well established, victims may either not know about these mechanisms, or may not feel confident in them. There is an argument for institutions to be more pro‐active in both preventing and detecting such behaviour, and providing support for the victims 4 …”
mentioning
confidence: 99%